Self-fragmentation among Yazidi women survivors of ISIS crimes (Raparin Journal of Humanities (RJH), 2024)
The Yazidi community faced undesirable and distressing experiences because of the war that included physical and sexual violence under the control of the terrorist organization ISIS. Therefore, the researcher formulated several research objectives, which are: to examine the level of self-fragmentation among Yazidi women who have survived ISIS crimes, those who lived under the authority of (ISIS) and those who escaped and did not live under the control of (ISIS).The researcher selected a sample that consisted of (400) Yazidi women who survived, and intentionally applied two research instruments to the research sample, the researcher built the self-fragmentation scale. The researcher accomplished both the face validity and construction validity and used Spearman-Brown, Gitman, and Alpha-Cronbach equations for reliability.The data is analyzed through Statistical Package for Social Sciences (SPSS). The research shows that The sample members have a fragmentation of the self, as well as the researcher found that there are differences in the fragmentation of the self according to the age variable and in favor of those under the age of forty years and there is a statistically significant difference in self-fragmentation between those who lived under the authority of ISIS and those who did not live under the authority of ISIS.Based on the current findings the researcher made several necessary recommendations and suggestions.